Analisis Pengungkapan Laporan Keuangan dalam Mendukung Pengambilan Keputusan Investor: Studi Kasus pada Laporan Keuangan PT Garuda Indonesia Tbk - Salwa Dwi Haniah; Haris Alrasyid Samosir; Randyka Surya Ramadhan; Fithriyyah Akhdiyatul Nabiilah; Muhamar Rajabillah Saputra (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
The objective of this study is to analyze the role of financial statement disclosure in supporting investor decision-making through a case study of PT Garuda Indonesia Tbk. This study employs a qualitative descriptive method using a literature review approach. Data were obtained from scientific journals, academic articles, the company’s financial statements, accounting standards, and various literature related to financial statement disclosure and investment decisions. An analysis of the company’s income statement, balance sheet, and cash flow statement was conducted to assess its financial condition and the relevance of this information to investors. The results indicate that PT Garuda Indonesia Tbk’s financial performance has experienced a significant decline in profits, leading to an unhealthy financial position characterized by a decrease in cash and operating cash flow, as well as an increase in the capital deficit. This situation indicates high financial risk for the company and is an important consideration for investors in making investment decisions. Therefore, the presentation of financial statements that are transparent, relevant, and in accordance with accounting standards is crucial for enhancing investor confidence and supporting the quality of investment decision-making.